Cervical conization and lymph node assessment for early stage low-risk cervical cancer. Issue 3 (March 2021) - Nica, Andra; Marchocki, Zbigniew; Gien, Lilian T; Kupets, Rachel; Vicus, Danielle; Covens, Allan
Abstract : Objective: There has been a contemporary shift in clinical practice towards tailoring treatment in patients with early cervical cancer and low-risk features to non-radical surgery. The objective of this study was to evaluate the oncologic, fertility, and obstetric outcomes after cervical conization and sentinel lymph node (SLN) biopsy in patients with early stage low-risk cervical cancer. Methods: We conducted a retrospective review in patients with early cervical cancer treated with cervical conization and lymph node assessment between November 2008 and February 2020. Eligibility criteria included patients with a histologic diagnosis of invasive squamous cell carcinoma, adenocarcinoma or adenosquamous carcinoma, International Federation of Gynecology and Obstetrics 2009 stage IA1 with positive lymphovascular space invasion (LVSI), stage IA2, or stage IB1 (⩽2 cm) with less than two-thirds (<10 mm) cervical stromal invasion. Results: A total of 44 patients were included in the analysis. The median age was 31 years (range 19–61) and 20 patients (45%) were nulliparous. One patient had a 25 mm tumor while the remaining patients had tumors smaller than 20 mm. Eighteen (41%) patients had LVSI. Median follow-up was 44 months (range 6–137). A total of 17 (39%) patients had negative margins on the diagnostic excisional procedure, and none had residual disease on the repeat cone biopsy. Three (6.8%) patients had micrometastases detected in the SLNs and underwent ipsilateral lymphadenectomy; all remaining non-SLN lymph nodes were negative. Six (13.6%) patients required more definitive surgical or adjuvant treatment due to high-risk pathologic features. There were no recurrences documented. Three patients developed cervical stenosis. The live birth rate was 85% and 16 (94%) of 17 patients had live births at term. Conclusion: Cervical conization with SLN biopsy appears to be a safe treatment option in selected patients with early cervical cancer. Future results of prospective trials may shed definitive light on fertility-sparing options in this group of patients.